Bisulfite Sequence Analyses Using CyVerse Discovery Environment: From Mapping to DMRs. Issue 3 (1st September 2016) - Song, Jawon; Zynda, Greg; Beck, Samuel; Springer, Nathan M.; Vaughn, Matthew W.
Abstract: Epigenetic modification of DNA through methylation is known to be involved in multiple biological processes such as gene suppression. However, the exact mechanism of how DNA methylations play their part is yet unclear. In mammals, CpG islands (CGI) have been studied extensively for their involvement in cancer. Whereas in plants, despite the fact that there are not only CpG but also CHG and CHH contexts of methylation, an efficient and easy‐to‐use pipeline to decipher these phenomena is still to be developed. Both ZED‐align and BisuKit are user‐friendly apps deployed on CyVerse infrastructure where users can use their bisulfite sequence files to run multiple command line‐based packages with minimal intervention. © 2016 by John Wiley & Sons, Inc.